"Bloody Wonder Woman!": Identity performances of elite women entrepreneurs on Instagram. (March 2022) - Heizmann, Helena; Liu, Helena
Critical scholarship has challenged traditional assumptions of entrepreneurship as a 'neutral' economic activity, demonstrating instead how entrepreneurship is a cultural phenomenon. In particular, enterprise culture has been exposed as fundamentally masculinist, so that women entrepreneurs are said to be measured against gendered values and ideals. What remains relatively unexplored, however, are the ways the identity performances of women entrepreneurs on social media reflect and reproduce inequalities that extend beyond gender. In this article, we examine how highly privileged Australian women entrepreneurs perform their identities on Instagram. In applying intersectionality theory, our study finds that the entrepreneurs produced idealised feminine identities by leveraging the intersections of white, elite-class, heteronormative, able-bodied power within a broader neoliberal discourse. In doing so, our analysis points to how romanticised ideals of women's economic empowerment in digital spaces may obscure the perpetuation of systemic and structural oppression.